(untitled) (Revista de Pesquisa: Cuidado é Fundamental, 2019)
Objective: The study’s purpose has been to delineate the clinical-epidemiological profile of patients undergoing cardiac catheterization; furthermore, to propose a management technology to create a database with information of epidemiological relevance. Methods: It is a retrospective study with a quantitative approach, which considers the databases and medical records of 1,890 patients who underwent cardiac catheterization at a hemodynamic unit from April 2014 to April 2016. Microsoft Office Excel® software was used to both organize and analyze the data. CAAE No. 55615616.0.0000.5282. Results: The average age was 61.45 years old. The majority of the assisted population is indicated by the National Regulation System (63%) with the following distribution: (52.86%) male and (47.14%) female. It was identified that 79.5% of the users have high blood pressure. It was found that the current strategy for monitoring the assisted users shows information deficiencies. Conclusion: The nursing consultation contributes to the improvement of the Sistema Único de Saúde (SUS) [Unified Health System] when capable of obtaining both relevant and determinant information for the professional nursing performance